Conflicts, poverty and human development in Northern Uganda - Justine Nannyonjo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
The long-running conflict in northern Uganda has led to major violations of human rights against civilians, destruction of infrastructure, reduced access to social services, and paralysed economic activity. Creating peace and fostering reconciliation in the region have not been successful either, thereby hindering development and relief activities, which are further constrained by insufficient funding, and lack of capacity at the district and community levels. The main challenges for reconstruction in northern Uganda are therefore to: (i) achieve peace and reconciliation (ii) provide basic social services to the affected areas (iii) strengthen government capacity to coordinate development and relief activities and (iv) harmonize interventions by the various stakeholders to achieve increased flexibility and transparency. – conflict ; insecurity ; poverty ; human development ; northern Uganda
Keywords: D74; O18; O55; H5; 330; Armut; Entwicklung; Uganda; Politischer Konflikt